Cationic surfactants as a non-covalent linker for oxidised cellulose nanofibrils and starch-based hydrogels. (1st April 2020) - Hossain, Kazi M. Zakir; Calabrese, Vincenzo; da Silva, Marcelo A.; Bryant, Saffron J.; Schmitt, Julien; Scott, Janet L.; Edler, Karen J.
Graphical abstract: Highlights: Cationic surfactants induce gelation of oxidised cellulose nanofibrils (OCNF). Electrostatic attraction causes increase in storage modulus of OCNF/surfactant gels. Addition of starch to the OCNF suggested formation of a network. Surfactants form stronger and more stable bridges between OCNF and starch helices. Abstract: Rheological properties of hydrogels composed of TEMPO-oxidised cellulose nanofibrils (OCNF)-starch in the presence of cationic surfactants were investigated. The cationic surfactants dodecyltrimethylammonium bromide (DTAB) and cetyltrimethylammonium bromide (CTAB) were used to trigger gelation of OCNF at around 5 mM surfactant. As OCNF and DTAB/CTAB are oppositely charged, an electrostatic attraction is suggested to explain the gelation mechanism. OCNF (1 wt%) and soluble starch (0.5 and 1 wt%) were blended to prepare hydrogels, where the addition of starch to the OCNF resulted in a higher storage modulus. Starch polymers were suggested to form networks with cellulose nanofibrils. The stiffness and viscosity of OCNF-Starch hydrogels were enhanced further by the addition of cationic surfactants (5 mM of DTAB/CTAB). ζ -potential and amylose-iodine complex analyses were also conducted to confirm surface charge and interaction of OCNF-starch-surfactant in order to provide an in-depth understanding of the surfactant-induced gel networks.